2014
DOI: 10.1093/bja/aeu153
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocking agents during electroconvulsive therapy: a review

Abstract: Electroconvulsive therapy (ECT) is associated with at least transient episodes of hypertension and tachycardia. Beta-blocking agents may be indicated to prevent cardiovascular complications and may shorten seizure duration. This review evaluates studies that used beta-blocking agents during ECT to determine which agent has the most favourable outcomes on cardiovascular variables and seizure duration. A Medline database search was made using the combined keywords 'adrenergic beta-antagonists' and 'electroconvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Even in a normal heart, ventricular dysfunction has been noted up to 6 h after ECT. [12][13][14][15][16][17][18] Rapid short-acting opioid analgesics and beta blockers also possess a sympatholytic effect and have recently been investigated as adjuvants during ECT 18,19 but many of them have been found to reduce seizure duration. The purpose of our study was to blunt the haemodynamic insult associated with ECT using dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Even in a normal heart, ventricular dysfunction has been noted up to 6 h after ECT. [12][13][14][15][16][17][18] Rapid short-acting opioid analgesics and beta blockers also possess a sympatholytic effect and have recently been investigated as adjuvants during ECT 18,19 but many of them have been found to reduce seizure duration. The purpose of our study was to blunt the haemodynamic insult associated with ECT using dexmedetomidine.…”
Section: Discussionmentioning
confidence: 99%
“…Esmolol hydrochloride (Brevibloc, Baxter Healthcare) is commonly used in clinical practice as an ultra-short-acting ␤ 1 -blocker (4,19,20,30,51). With an elimination half-life of Ͻ10 min due to metabolism by red blood cell esterases and low lipid solubility, it is often administered as a bolus injection before transient stimulation such as laryngoscopy, cranial pinning, and electroconvulsive therapy (5,58). Indeed, comparative effectiveness studies in anesthetized patients have demonstrated that bolus injections of 20 -200 mg of esmolol attenuate HR responses to laryngoscopy and endotracheal intubation (13,14,29,33,41,43).…”
Section: New and Noteworthymentioning
confidence: 99%
“…It is beyond the scope of this article, but efforts have been made to use preventive strategies to mitigate the cardiac risk associated with ECT in high-risk patients, such as improved identification 14 or therapeutic strategies, such as beta-blockers. 33,34 It should be pointed out that patients who did not develop new hscTnI elevation after ECT, but had already elevated baseline hscTnI values, may be at increased long-term cardiovascular risk even if they did not experience myocardial injury during ECT.…”
Section: Discussionmentioning
confidence: 99%